OPTIMALISASI KINERJA PEGAWAI DI BIDANG BINAMARGA PADA DINAS PEKERJAAN UMUM DAN TATA RUANG KABUPATEN SUMEDANG - Hermayanty, Irma; Purnama, Acep; Ikhsan, Muhammad; Nuraini, Nica; Nurdini (LPPM UNSAP & FISIP UNSAP, 2024)
This research aims to find out how the optimization of employee performance in the Bina Marga field at the Sumedang Regency Public Works and Spatial Planning Office, obstacles in optimizing employee performance, and efforts to improve performance optimization. The method used in preparing this research report is descriptive qualitative method. The sampling technique used was purposive sampling, with 3 research informants: Head of Division, Functional Officer, and General Functional. Data collection techniques through literature studies and field studies. In analyzing the data used the Miles and Huberman model with steps: data reduction, data presentation, conclution drawing/verification, and triangulation. Based on the results of the study, it shows that the optimization of work in the Highways Division is quite good as seen from the optimal 4 dimensions that have found the results, namely, work quality, ability, initiative, and communication but there is one dimension that is less than optimal, namely accuracy of work. The results show that in the dimension of work accuracy in improving the optimization of employee performance, several indicators of research findings are not optimal, namely the timeliness of work is not optimal, the accuracy of completing tasks is not optimal, and working hours are over time where work in one day is not completed properly so that overtime is needed. The obstacles in optimizing performance based on the results of the study include in terms of individual factors, namely the high workload of employees. Organizational factors are the removal of sections in the organizational structure in the Bina Marga field. Environmental factors that hinder are the lack of facilities and infrastructure and the use of technology that is not optimal. The efforts made are by planning starting from employee development, providing training to employees to improve performance. provide motivation, clarify the objectives of the work given. facilitate communication within the organization and individually with employees such as optimizing communication tools that support work.